Invasion of Aureobasidium Pullulans in kidney and eyes of immunosuppressed patients (Indian Journal of Case Reports, 2019)
There were series of proven cases revealing opportunistic fungal infections in the cornea, cutaneous, subcutaneous and renal transplant patients. Renal involvements of opportunistic mold in immunocompromised especially in renal transplant recipients have remained a significant problem and a major cause of death worldwide. However, extensive literature reviews revealed no case of invasion in urolithiasis and rarely reported in endophthalmitis. Here, we report the case series of two rare cases related to a dematiaceous fungus, Aureobasidium pullulans. Both had an atypical presentation. Possible modes of entry and dissemination were discussed. Invasive surgical procedures, frequent uses of antibiotics and steroid could possibly predispose to its invasion in immunocompromised patients. This organism was identified through molecular techniques since culture yielded no growth. There was a good outcome following surgical intervention in both cases.